HUBUNGAN DIMENSI KEPRIBADIAN BIG FIVE TERHADAP PEMBENTUKAN ORGANIZATIONAL CITIZENHSIP BEHAVIOR (OCB) PADA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN ROKAN HULU - Zurina; Arrafiqur Rahman (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2020)
This study aims to determine the dimensions of the personality of the big five towards the formation of Organizational Citizenship Behavior (OCB) on the employees of the Ministry of Religion Office of Rokan Hulu Regency. The measuring instrument used in this study was a questionnaire which was divided into 2 scales, namely, the scale dimension of the big five personality consisted of 25 statements and the OCB scale consisted of 15 statements. The number of respondents in this study were 34 people. Data analysis technique used in this study was to use Pearson Product Moment correlation analysis with the help of SPSS 18.0 application in its calculations. The results showed that the five dimensions of the big five personality were found to be significantly related to the formation of OCB in the Rokan Hulu District Ministry of Religion Office employees. There is a significant correlation with conscientiousness of 0.665 with a significance of 0,000 <0.05, for the extraversion dimension of correlation coefficient value of 0.787 with a significance of 0,000 <0.05, the neuroticsm dimension of 0.458 with a significance of 0.006 <0.05, the dimension of openness of 0.578 with a significance of 0,000 <0.05 and agreeableness dimensions of 0.750 with a significance of 0,000 <0.05 to the formation of OC